Thermal stability and entropy generation of unsteady reactive hydromagnetic Powell-Eyring fluid with variable electrical and thermal conductivities - S.O. Salawu; A.R. Hassan; A. Abolarinwa; N.K. Oladejo (Alexandria Engineering Journal, 2019)
Theoretical analysis of thermal stability and inherent irreversibility of reactive hydromagnetic Powell-Eyring fluid flow in a fixed vertical channel with variable electrical and thermal conductivities is examined. The conducting reactive fluid is influenced by gravity and axial pressure gradient under bimolecular kinetic rate law. Ignoring the material assumptions, the governing dimensionless equations are solved by finite semi-discretization difference scheme along with integration Fehlberg Runge-Kutta method. The results for the momentum and heat equations, Bejan number, thermal runaway, entropy generation and current density are graphically presented under different thermophysical parameters. The computational results for the shear stress and heat transfer at the wall is also presented and discussed quantitatively. It was observed that the parameter which enhance the rate of entropy generation also augment Bejan number with large pitch ratio. Hence, entropy generation can be minimized at low dissipation and material variables. Keywords: Thermal runaway, Reactive fluid, Chemical kinetic, Variable conductivity, Non-Newtonian